1999
DOI: 10.1034/j.1399-3054.1999.105402.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, immunolocalization, cryoprotective, and antifreeze activity of PCA60: A dehydrin from peach (Prunus persica)

Abstract: Dehydrins are glycine-rich, hydrophilic, heat-stable proteins isoelectric focusing followed by size exclusion. Purified PCA60, as well as crude protein extract, preserved the in 7itro and are generally induced in response to a wide array of enzymatic activity of lactate dehydrogenase after several environmental stresses. In previous research (Artlip et al.freeze-thaw cycles in liquid nitrogen. PCA also exhibited 1997, Plant Molecular Biology 33: 61-70), a full-length dehydrin gene, ppdhn1, was isolated from pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
220
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(229 citation statements)
references
References 38 publications
8
220
1
Order By: Relevance
“…Previously, we showed that V. riparia K 2 and YSK 2 do not have any AFP activity (Livernois et al, 2009). In contrast, two other studies showed that PCA60 (a peach Y 2 K 9 dehydrin; Wisniewski et al, 1999) and a putative dehydrin from F. suspensa (Simpson et al, 2005) have AFP activity. At the time, we thought that the two K-segments may have been insufficient to bring about AFP activity.…”
Section: Ice Recrystallization Inhibition By Dehydrinsmentioning
confidence: 87%
See 2 more Smart Citations
“…Previously, we showed that V. riparia K 2 and YSK 2 do not have any AFP activity (Livernois et al, 2009). In contrast, two other studies showed that PCA60 (a peach Y 2 K 9 dehydrin; Wisniewski et al, 1999) and a putative dehydrin from F. suspensa (Simpson et al, 2005) have AFP activity. At the time, we thought that the two K-segments may have been insufficient to bring about AFP activity.…”
Section: Ice Recrystallization Inhibition By Dehydrinsmentioning
confidence: 87%
“…Two previous reports suggested that dehydrins also have the ability to shape ice crystals and prevent their growth at moderate subzero temperatures (Wisniewski et al, 1999;Simpson et al, 2005). This activity was suggested to come from the dehydrin present in peach (Prunus persica) bark (PCA60; Wisniewski et al, 1999) and from a partially purified and characterized Forsythia suspensa protein that may contain K-segments (Simpson et al, 2005).…”
Section: Potential Afp Activity Of Dehydrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…DHNs localize primarily to the nucleus or cytoplasm (Houde et al, 1995;Bracale et al, 1997), but studies also corroborate their presence either in the plasma membrane (Danyluk et al, 1998), endoplasmic reticulum (Neven et al, 1993), chloroplast (Wisniewski et al, 1999), mitochondria (Borovskii et al, 2002) or even in the vacuole (Heyen et al, 2002). DHNs may thus be expressed either constitutively [e.g.…”
Section: Structure and Functional Studies Of Dhnamentioning
confidence: 87%
“…Arabidopsis DHNX] or confined to the root tip (ERD14 and LTI29), vascular tissues (ERD14, LTI29 and RAB18) and stomatal guard cells (RAB18). DHNs accumulate within vascular tissues (Godoy et al, 1994;Houde et al, 1995;Danyluk et al, 1998;Nylander et al, 2001), pollen sacs, guard cells and root meristems (Nylander et al, 2001), endosperm and zygotic embryos of mature seeds, developing root primordia (Godoy et al, 1994;Bracale et al, 1997), wheat crown tissues (Houde et al, 1995) and peach shoots (Wisniewski et al, 1999). DHNs found only in the cytosol include those of C. plantagineum DSP16 (Schneider et al, 1993) and rice RAB21 (Mundy and Chua, 1988).…”
Section: Structure and Functional Studies Of Dhnamentioning
confidence: 99%